THE STRATEGIES OF NEGATIVE AND POSITIVE POLITENESS USED BY BRAD’S UTTERANCES IN FRONT OF THE CLASS MOVIE - Ayu Susana; M. Bahri Arifin; Ririn Setyowati (Fakultas Ilmu Budaya Universitas Mulawarman, 2022)
ABSTRACTPoliteness plays an important role in keeping a conversation run well. However, there are still some difficulties in playing polite and proper language for communication. Considering these phenomena, a study of politeness strategy was conducted. In this research, the researcher analyzed the use of politeness strategies especially positive and negative politeness in Front of the Class movie. The purposes of this research were to find out the kinds of positive politeness strategies, negative politeness strategies, and factors influencing Brad Cohen in using positive and negative politeness strategies in the movie. The research method in this research was descriptive qualitative research, the theory of politeness strategies by Brown and Levinson (1987) was used to analyze the four two of politeness strategy. The result of this research showed that there were twenty-seven utterances represented two politeness strategies used by Brad Cohen in Front of the class movie. Twenty-one utterances represented a positive politeness strategy and six utterances represented a negative politeness strategy. In positive politeness strategy 6: avoid disagreement and strategy 11: be optimistic are strategies that many researchers find in the film. Meanwhile, in negative politeness, they are only 2 strategy that the researcher found in the movie they are strategy 3: be pessimistic and strategy 5: give deference which both had the same amount of data. There are 2 factors influencing the choice of politeness strategies used by Brad Cohen in Front of the class movie. They are payoff and the circumstances. Twenty-seven utterances categorized as politeness strategies, twenty-one of them belong to positive politeness strategy, so that positive politeness strategy is the most dominantly used by Brad Cohen in Front of the class movie.Keyword: Negative Politeness, Positive Politeness, Factor Influence, Front of the class movie ABSTRAKKesopanan memainkan peran penting agar percakapan tetap berjalan dengan baik. Namun demikian, masih terdapat beberapa kesulitan dalam memainkan bahasa yang sopan dan pantas untuk komunikasi. Melihat fenomena tersebut, maka dilakukan studi tentang strategi kesantunan. Dalam penelitian ini, peneliti menganalisis penggunaan strategi kesantunan khususnya kesopanan positif dan negatif dalam film Front of the class. Tujuan dari penelitian ini adalah untuk mengetahui macam-macam strategi kesantunan positif, strategi kesantunan negatif, dan faktor-faktor yang mempengaruhi Brad Cohen dalam menggunakan strategi kesantunan positif dan negatif dalam film tersebut. Metode penelitian dalam penelitian ini adalah penelitian kualitatif deskriptif, teori strategi kesantunan oleh Brown dan Levinson (1987) digunakan untuk menganalisis dua jenis strategi kesantunan. Hasil penelitian menunjukkan bahwa terdapat dua puluh tujuh ujaran yang merupakan dua strategi kesantunan yang digunakan oleh Brad Cohen di film Front of the class. dua puluh satu ucapan mewakili strategi kesantunan positif dan enam ucapan mewakili strategi kesopanan negative. Dalam kesantunan positif, strategi 6: hindari ketidaksepakatan dan strategi 11: optimis adalah strategi yang banyak ditemukan peneliti dalam film tersebut. Sedangkan dalam kesantunan negatif, hanya ada 2 strategi yang peneliti temukan dalam film tersebut yaitu strategi 3: pesimis dan strategi 5: memberi hormat yang keduanya memiliki jumlah data yang sama. Ada 2 faktor yang mempengaruhi pemilihan strategi kesantunan yang digunakan oleh Brad Cohen dalam film Front Class. Mereka adalah imbalan dan keadaannya. Dua puluh tujuh ujaran dikategorikan sebagai strategi kesantunan, dua puluh satu diantaranya termasuk dalam strategi kesantunan positif, sehingga strategi kesantunan positif paling dominan digunakan oleh Brad Cohen dalam film Front of Class.Keyword: Kesopanan negatif, kesopanan positif, factor yang mempengaruhi, film Front of the Class